(untitled) (Journal of Asian Development Studies, 2017)
Cities are center of economic growth, creativity and modernization. The economic structure of cities is of immense importance not only from the point of view of city development and growth but also for the national development and growth. To choose the suitable estimation technique prior to estimation of coefficients of variables determining the size of a city, several pre-estimation tests are conducted. The results of pooled vs. fixed effect test supported fixed effect model. Similarly, test performed to select among pool and random effect model favored random effect model. In both tests, pool model is found inappropriate for estimation. Now to choose between the two suggested models, fixed and random effect, Hausman (1978) test is applied with the null hypothesis that fixed effect model and random effect model estimators do not differ substantially and in such a case random effect model is preferred, otherwise fixed effect model is more appropriate. The result of Hausman test significantly rejects the null hypothesis against the alternative one. Thus fixed effect model is selected for estimating the regression model. The results mentioned that expansion of informal sector and migration inflows causes economic size of city to be larger. Positive amenities as reflected by the provision of education, health and banking services also found to have a significant impact in expending city size, on the other side negative amenities like congestion and crime rate of a city contract city’s economic size. Volume of trade (import and exports) has a positive significant impact in enhancing city growth economically. Finally, the effect of being a port city is also significant and positive. A port is more prone to increased concentration of trade activities and industries generating substantial employment opportunities which in turn enhance consumption and production.